Intervention in The Elderly Patients With Type 2 Diabetes Mellitus With Diabetic Foot Ulcer: A Systematic Review - Anggraini, Ria; Agushyibana, Farid; Rachma, Nurullya (Universitas Respati Yogyakarta, 2020)
The prevalence of people with diabetes mellitus (DM) has increased by 6.9% to 8.5% in 2018. DM type 2 is increasing for the elderly, such as peripheral neuropathy, nephropathy and diabetic neuropathy. Peripheral neuropathy increases the risk of increased diabetic foot ulcer (DFU). Intervention of appropriate diabetic foot ulcer intervention is needed to improve quality of life and reduce the incidence of amputations. The purpose of this study is to review the effective interventions to prevent and reduce the rate of DFU. This study was carried out by following the standard guidelines in making a systematic review of the